Total Plate Count (TPC) Test of Tofu After Storage With The Addition Of Crown of God Fruit Flour (Phaleria macrocarpa Scheff. Boerl.) - Ade Vera Yani; Idealistuti Idealistuti; Dasir Dasir; Januar Triwobowo (Journal of Global Sustainable Agriculture, 2022)
Tofu is one of the foods in great demand by the public with affordable prices and fulfils the needs of protein in the body. The main obstacle to tofu production is concise shelf life. Tofu has a shelf life of one to two days without preservatives even though it is stored at a low temperature, which is a maximum temperature of 15°C. The way to reduce food ingredients' damage could be using natural origin and synthetic preservatives. The crown of god fruit can be used as a preservative of food from nature because it contains antioxidants and antimicrobials. This study aims to determine the Total Plate Count (TPC) of tofu stored with the fruit flour of the crown of god fruit. The method used is a Non-Factorial Group Randomized Design (RAK) consisting of six levels of treatment and repeated four times. The soaking of tofu in various powders of god's crown fruit as a natural preservative has a very noticeable effect on the Total Plate Count (TPC) after five days of storage. The highest number of microbes in the M0 treatment (without the provision of god's crown fruit flour) with an average value of 2.73x102 CFU/g and the lowest number of microbes in the M4 treatment (0.125g) with an average value of 0.93x102 CFU/g.